2016
DOI: 10.1016/j.ejpal.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and attention deficits as possible mechanisms underlying impaired emotion recognition in intimate partner violence perpetrators

Abstract: a b s t r a c tSeveral studies have reported impairments in decoding emotional facial expressions in intimate partner violence (IPV) perpetrators. However, the mechanisms that underlie these impaired skills are not well known. Given this gap in the literature, we aimed to establish whether IPV perpetrators (n = 18) differ in their emotion decoding process, attentional skills, and testosterone (T), cortisol (C) levels and T/C ratio in comparison with controls (n = 20), and also to examine the moderating role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The eyes test requires an advanced brain system (i.e., visual and emotional processing, decoding, recognition), which not only involves new ways of thinking, but also the recognition of complex emotional states (Thye, Murdaugh, & Kana, ). However, specific underlying mechanisms through which inattention deficits/distractibility influence emotion‐decoding abilities in IPV perpetrators (Romero‐Martínez et al ., ) were not specifically tested in the present study. There may be a direct association between these variables, or this association might be mediated by other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eyes test requires an advanced brain system (i.e., visual and emotional processing, decoding, recognition), which not only involves new ways of thinking, but also the recognition of complex emotional states (Thye, Murdaugh, & Kana, ). However, specific underlying mechanisms through which inattention deficits/distractibility influence emotion‐decoding abilities in IPV perpetrators (Romero‐Martínez et al ., ) were not specifically tested in the present study. There may be a direct association between these variables, or this association might be mediated by other factors.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of the present study was to evaluate the differences between SBIP and SBIP + Individualized Motivational Plan (IMP) in IPV perpetrators’ cognitive outcomes after ending both interventions. Based on the evidence showing that SBIP produces cognitive‐emotional changes in IPV perpetrators (Romero‐Martínez, Lila, & Moya‐Albiol, ), and SBIP + IMP demonstrates higher efficacy than SBIP in producing changes in IPV perpetrators, with the former group showing lower self‐reported physical violence and greater reductions in the risk of recidivism assessed by therapists compared to the SBIP group (Lila et al ., ), our initial hypothesis was as follows: (1) SBIP and SBIP + IMP would produce improvements in emotion‐decoding abilities and empathy; and (2) SBIP + IMP, compared to SBIP alone, would be more likely to increase participants’ commitment to the dynamics and activities of the intervention, dedicating more attention and effort to the activities proposed (Lila et al ., ), and thus produce greater improvement in cognitive‐emotional abilities.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, our results suggest that a positive bond and agreement on the goals and tasks of the intervention between therapists and participants could facilitate offenders’ motivation to change. Previous studies have proposed that the working alliance between the participant and the therapist is not only able to modify their cognitive processing but also their actions and affective state ( Brown and O’Leary, 2000 , Romero-Martínez et al, 2016 ). In this regard, Brown and O’Leary (2000) found that the working alliance, observationally assessed, was related to a decrease in psychological and physical aggression.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was developed within the Contexto Program, a psychoeducational and community-based treatment program (mandatory for male abusers) at the Department of Social Psychology, University of Valencia, Spain (see Lila, Oliver, Catalá-Miñana, & Conchell, 2014). The main objective of the program is to reduce risk factors and increase protective factors for IPV, taking into account four levels of analysis: individual, interpersonal, situational, and macrosocial (Catalá-Miñana, Lila, & Oliver, 2013;Gracia, López-Quilez, Marco, Lladosa, & Lila, 2015;Lila, Gracia, & Herrero, 2012;Lila, Gracia, & Murgui, 2013;Rodríguez, Gracia, & Lila, 2016;Romero-Martínez, Lila, & Moya-Albiol, 2016;Vargas, Lila, & Catalá-Miñana, 2015). The sociodemographic characteristics of the sample were as follows: average age was 39.54 years (SD = 11.23); the average annual income was between 6,000 and 12,000 euros.…”
Section: Participantsmentioning
confidence: 99%